Structural And Phase Composition Of Fullerene Films Deposited By High-Power Ion Beams; Bulletin of the Russian Academy of Sciences. Physics; Vol. 72, № 7 - Struts V. K.; Matvienko V. M.; Petrov A. V.; Ryabchikov A. I. Aleksandr Ilyich; Usov Y. P. Yuri Petrovich; Renk T. J. (2008, 2008)
В фонде НТБ ТПУ отсутствует